Development and Characterization of a Modified Vaccinia Ankara Vaccine Candidate Expressing the SARS-CoV-2 Spike Glycoprotein - Khumalo, Fezokuhle Ncedile (Department of Pathology, 2023)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2, SARS-CoV-2. Given the ongoing COVID-19 pandemic and the continued evolution of the virus to escape host immunity, new vaccines and refinement of first-generation vaccines to improve protection against SARS-CoV-2 variants of concern is vital. In Africa, the cost of vaccine manufacturing as well as the scarcity in resources for storage and distribution have all contributed to the inequitable access to vaccines and heavy reliance on donations. Modified Vaccinia Virus Ankara (MVA) is a low-cost production vector platform which is suitable in this context. This project falls into a bigger study where our group compared different vector platforms, including MVA. The project serves as a proof of concept that this platform can be used to produce vaccines encompassing different variants of SARS-CoV-2 as they emerge. The most recent variant, Omicron, has proven to be highly immune evasive and demonstrates this need well. As the virus mutates, the variants of concern each present with differing characteristics and subsequently differ in immunogenicity and pathogenicity. Sub-Saharan Africa has been ransacked by the pandemic, resulting in loss of lives and livelihoods; the effects of which will undoubtedly be felt for decades to come. This study had two aims: 1. The development of a candidate vaccine, MVA-SARS-CoV2-S∆TM by using the widely used MVA platform and poxvirus recombinant vaccine strategies used in our research group, 2. The testing of this vaccine's immunogenicity in mice. The MVA-based vaccine was constructed by infection of BHK21 cells with wildtype MVA, and transfection with transfer vector pMVA-FNK2. The transfer vector contains a truncated form of the SARS-CoV-2 spike glycoprotein gene, the vaccinia virus host-range gene K1L and reporter gene eGFP, flanked by gene sequences to allow homologous recombination into MVA. The presence of the K1L gene in the recombinant virus allowed for selection by passaging in RK13 cells, which were not permissive for the parent MVA. Following the potentially successful isolation, the recombinant MVA-SARS-CoV2-S∆TM was validated and characterized by PCR, Sanger sequencing, Western blot analysis and immunofluorescence, which all confirmed the presence and expression of the spike protein. Large scale propagation of the vaccine was done in RK13 cells, and the stock was titrated to yield a titre of 3.9 x 106 ffu/ml. Balb/c mice were inoculated three times with MVA-SARS-CoV2-S∆TM at a dose of 3 x 105 to assess immunogenicity of the vaccine. Results from the immunogenicity assessments demonstrated that the vaccine induced T-cell responses shown by an enzyme-linked immunosorbent spot (ELISpot) assay. An enzyme-linked immunosorbent assay (ELISA) confirmed the ability of MVA-SARSCoV2-S∆TM to induce increasing titres of binding antibodies in mice over a period of 56 days. However, the vaccine did not induce neutralizing antibodies against a matched SARS-CoV-2 pseudovirus, highlighting the need for further refinement of the vaccine. In conclusion, recombinant MVA expressing a truncated SARS-CoV-2 spike protein was successfully constructed and tested for immunogenicity in mice. The candidate vaccine induced good T-cell responses and binding antibodies, but not neutralizing antibodies. This study provides additional evidence that MVA can be used as a platform for a SARS-CoV-2 vaccine, as has been previously demonstrated by others, and this could potentially be adapted for emerging variants of concern. This work also allows for the direct comparison of the MVA platform to other platforms employed by our group (DNA and plant-based subunit) as SARS-CoV-2 vaccines.